Construction of 3D carbon fiber/carbon nanotube/silicone rubber nanocomposites for stretchable conductors through interface host-guest dendrimers. (22nd March 2021) - Lu, Yao; Wang, Jincheng; Wang, Le; Zhao, Dongqing; Song, Shiqiang
Abstract: Stretchable carbon-based conductive polymer composites have broad application prospects in wearable electronic devices such as human motion monitoring. However, the conductive network with weak internal bonding of existing flexible sensors tends to undergo irreversible changes during the deformation process, which makes the sensor performance unstable and limits its application in actual production. Therefore, it is necessary to design a strategy to improve the interaction between the components of conductive polymer composites and promote the large-scale use of flexible sensors. In this article, a novel and stable interconnection network (CF-CD/CNT-Ad) structure based on the carbon fiber and carbon nanotube has been fabricated by a host-guest dendrimer self-assembled method. The silicone rubber (SR) was then filled into the CF-CD/CNT-Ad network to prepare a stable and sensitive SR flexible sensor. The flexible sensor showed high strain sensitivity and excellent stability in the detection of human motion behaviors under low strain. In addition, the flexible sensor also possessed adjustable and high electrical conductivity (148–957 S/cm) and excellent mechanical properties, endowing it with a broad application in human motion monitoring and other fields. Graphical abstract: Image 1 Highlights: Novel 3D skeleton structure (CF-CD/CNT-Ad) based on the carbon fiber and carbon nanotube has been fabricated by a host-guest dendrimer self-assembled method. Interconnected skeleton (CF-CD/CNT-Ad) was used as current transfer path to made the silicone rubber composite material have high electrical conductivity. The conductivity of the silicone rubber composite can be adjusted by changing the loading rate of CNT-Ad. The silicone rubber composite material showed high strain sensitivity and excellent stability in the detection of human motion behavior.